Electronic modulation of cobalt phosphide by lanthanum doping for efficient overall water splitting in alkaline media. Issue 41 (16th June 2022) - Kim, Daekyu; Yuan, Yuan; Lee, Lawrence Yoon Suk
Abstract : The La-doping regulates the electronic structure of CoP, promoting its HER and OER activities. A La–CoP-based water electrolyzer requires a cell voltage of 1.608 V at 10 mA cm −2 in alkaline media, which outperforms a noble metal-based electrolyzer. Abstract : The development of efficient electrocatalysts for water splitting is needed to boost green hydrogen production. Herein, a ZIF-67-derived La-doped CoP (La–CoP) is prepared by a facile solvothermal–phosphorization process as an efficient bifunctional water-splitting catalyst. The introduction of La into CoP enables the modulation of the electronic configuration of Co and P, facilitating the charge transfer and thus lowering the energy barrier of the rate-limiting step to catalyze oxygen and hydrogen evolution reactions (OER and HER). The optimized La–CoP delivers good OER and HER activities as manifested by small overpotentials of 270 and 109 mV, respectively, to reach the current density of 10 mA cm −2 . The electrolyzer constructed using La–CoP as both cathode and anode requires a cell voltage of 1.608 V at 10 mA cm −2 in alkaline media, which outperforms a noble metal-based (Pt/C and RuO2 ) electrolyzer. This work provides useful perspectives for fabricating efficient electrocatalysts by modulating the electronic structure of active sites.